2022
DOI: 10.1007/s10671-022-09318-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of professional teaching videos induction and online focused group discussion on the development of teacher competences

Abstract: This study investigated the effect of video-based teaching practice followed by focused group discussion via electronic collaborative discussion forum (ECDF) on the development of teacher competences. The trend of change on teacher competences of 30 Iranian English as foreign language teachers was traced before and after treatment on quantitative and qualitative measures. First, a newly designed and validated teacher assessment questionnaire named Teacher Balanced Score Card (TBSC) was used to quantitatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In response, several scholars conducted extensive research during the pandemic on addressing educational challenges and maximizing current opportunities [ [26] , [27] , [28] , [29] , [30] ]. Studies have shown that due to the emergency rollout of online education, a lack of time for training and online simulations occurred and many teachers and students did not have time to adapt to the new teaching model [ 31 ]. In the face of the challenges, some scholars have proposed that teachers adjust course subjects, change teaching methods, and become proficient in online teaching facilities.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…In response, several scholars conducted extensive research during the pandemic on addressing educational challenges and maximizing current opportunities [ [26] , [27] , [28] , [29] , [30] ]. Studies have shown that due to the emergency rollout of online education, a lack of time for training and online simulations occurred and many teachers and students did not have time to adapt to the new teaching model [ 31 ]. In the face of the challenges, some scholars have proposed that teachers adjust course subjects, change teaching methods, and become proficient in online teaching facilities.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…In this view, the second phenomenon to be examined is the competences of higher education staff. Many scientific works investigate this topic from various points of view (e.g., [20][21][22][23][24], etc.). According to Adamonien ė and Petrauskien ė [25], the modern HEI needs leaders and teachers who are able to creatively and innovatively identify and tackle the problems arising in an institution, and who possess the competences of leadership, management of changes, strategic thinking, and so on (p. 6).…”
Section: Introductionmentioning
confidence: 99%